Frequency of Cesarean Section in Patients Presenting with Non-Reactive Cardiotocography (CTG) - Asma Unar, Aneela, Zakia Zaheen, Maria, Shazia Ahmed Jatoi, Fozia Irum, Kiran Aamir, Aasma Naz, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Aim To determine frequency of cesarean section in patients presenting with non-reactive cardiotocography. Study Design: Descriptive study Place and Duration: Obstetrics and Gynaecology Unit-II at Peoples University Hospital Nawabshah. Feb 2021-August 2021 Methods: This study included 156 women had age 20-45 years admitted to the labour room through OPD and ER with uterine contractions. Antepartum and intrapartum CTG revealed abnormal results. Physical examination and CTG determined delivery mode. SPSS v25.0 examined and entered data. Chi-square was used post-stratification. Significant p-values were <0.05. Results: There were 82(52.6%) patients were in 18-30 years age group and 74(47.4%) were in 31-40 years age group. According to gestational age distribution, 86(55.1%) were from 37-38 weeks gestational age group and 70(44.9%) from 39-40 weeks gestational age group. Majority of the patients 97(62.2%) had rural residence and 59(37.8%) from urban area. Among all 11(7.1%) were obese and 19 (12.2%) had anemia. We found that 58(37.2%) cases had low income, while 42(26.9%) and 56(35.9%) had middle income and high income respectively. Frequency of C-section was found in 72(46.2%). Conclusion: Due to the high false positive rate of cardiotocography monitoring in labor, women are more likely to have a caesarean section. Other tests, such as fetal scalp electode and fetal pH, should be done to diagnose fetal distress before having one. Keywords: C-section, Non-reactive cardiotocography, Anemia, Obesity